Small Groups in the Church: A Handbook for Creating Community - Kirkpatrick, Thomas G. (Rowman & Littlefield Publishers, 1995)
This planning and leader training handbook offers a distinctive broad-based, small-group approach to building community. From the Jewish havurot to Christian koinonia, you will gain a thorough understanding of community, learn how to plan an effective small-group ministry, how to select and train leaders for all kinds of small groups, and how to start small groups that are a part of and not apart from their congregations. Appendices provide an overview of the sociological, psychological, and biblical theological literature on community and a wealth of presentation and leader training resources.